Exploring the Stone-Walled Structures of the Suikerbosrand: a Study on Location, Visibility and Political Rankings - O'Malley, Caitlin (My University, 2015)
The Suikerbosrand Nature Reserve has a number of Iron Age stone-walled structures situated in the landscape. The most recent stone-walled structures – the Group II stone-walled structures – date between the 17th and 19th Centuries, and have the highest potential for political stratification. This study aimed to identify political and social structures in the Suikerbosrand Group II sites, using Geographic Information Systems (GIS) and visibility analyses to establish an index for social and political rank. Links were identified between socially constructed landscapes, political hierarchies, economic control of resources and trade, and the interactions between site formation and visibility. A complex construction of social and political indices was identified, and a number of observations on social and political interactions were concluded.
Keywords: Stone-walled Structures, Iron Age, Southern Gauteng, GIS, Suikerbosrand Nature Reserve